Design, Synthesis, and Biological Evaluation of Novel Piperazine Derivatives Incorporating Thiazole Scaffolds - Yadav, Karmvati; Sharma, Priyanka (Journal of Neonatal Surgery, 2025)
This research investigates the synthesis, structural characterization, and biological evaluation of novel piperazine derivatives incorporating thiazole scaffolds. Twenty compounds (5a–8e) were synthesized, and their structures were confirmed through IR spectroscopy, mass spectrometry (MS), and nuclear magnetic resonance (NMR) spectroscopy. The synthesized compounds featured diverse halogen and sulfur substituents to explore their effects on biological activity. Antimicrobial activity was evaluated against Staphylococcus aureus and Escherichia coli, while anti-inflammatory activity was tested using the carrageenan-induced rat paw edema model. Bromine-substituted derivatives, such as compounds 5b and 8b, exhibited the highest antimicrobial potency with minimum inhibitory concentrations (MICs) of 12.5 µg/mL and 16 µg/mL, respectively. These results highlight the beneficial role of halogenation, particularly bromination, in enhancing antimicrobial efficacy by improving lipophilicity and membrane interaction. Anti-inflammatory activity ranged from 60% to 75% inhibition, with 8b showing the highest inhibition at 75%, suggesting that certain structural modifications, including halogen and sulfur substitution, significantly improve therapeutic potential. Overall, this study demonstrates that structural modifications, particularly the introduction of halogens, sulfur, and acyl groups, can significantly influence the biological activities of piperazine-thiazole derivatives, offering insights into the design of new antimicrobial and anti-inflammatory agents.